2022
DOI: 10.3390/polym14112204
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Effect of ZIF-67-Derived Hollow NiCo-LDH and MoS2 on Enhancing the Flame Retardancy of Thermoplastic Polyurethane

Abstract: In this work, a novel three-dimensional (3D) hollow nickel-cobalt layered double hydroxide (NiCo-LDH) was synthesized using zeolitic imidazole framework-67 (ZIF-67) as a template, and then utilized to functionalize molybdenum disulfide (NiCo-LDH/MoS2) via electrostatic force. Flame retardant thermoplastic polyurethane (TPU) composites were prepared by the melt blending method. Compared to pure TPU, NiCo-LDH/MoS2 filled TPU composite was endowed with a decrease of 30.9% and 55.7% of the peak heat release rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The XRD spectrum of pure TPU has a broad peak at around 24.8°and other TPU composites show additional characteristic peaks in addition to the peak at around 24.8°after combustion. It can be seen from the XRD patterns of the TPU/CoMn-LDH composites that the characteristic peaks of Co 2 O 3 spinel appear at around 27.5°, 31.1°, 38.4°, CoO spinel at around 36.5°, 42.2°, [13,24] Mn 3 O 4 spinel at around 18.2°, 32.4°, 44.4°, 20.2°. 21.5°, 36.5°, [41] indicating that the elements Co and Mn were oxidised to form metal oxides during the combustion process.…”
Section: Analysis Of Residual Charmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD spectrum of pure TPU has a broad peak at around 24.8°and other TPU composites show additional characteristic peaks in addition to the peak at around 24.8°after combustion. It can be seen from the XRD patterns of the TPU/CoMn-LDH composites that the characteristic peaks of Co 2 O 3 spinel appear at around 27.5°, 31.1°, 38.4°, CoO spinel at around 36.5°, 42.2°, [13,24] Mn 3 O 4 spinel at around 18.2°, 32.4°, 44.4°, 20.2°. 21.5°, 36.5°, [41] indicating that the elements Co and Mn were oxidised to form metal oxides during the combustion process.…”
Section: Analysis Of Residual Charmentioning
confidence: 99%
“…[9,10] Studies have shown that LDH can also work with other flame retardant effect materials to improve the fire safety performance of composites, for instance graphene [11] and MoS 2 . [12] Qian et al [13] investigated the flame retardant properties of MoS 2 and LDH by hydrothermal synthesis and showed that the nanomaterial hybridization not only made LDH more dispersed in the collective TPU material, but also the total heat released during combustion and the amount of smoke produced are greatly reduced. Discovered by Gogotsi et al in 2011, MXene is a twodimensional material that has attracted much attention for its excellent properties and it has the advantages of high specific surface area, excellent thermal stability, and good catalytic performance, hence MXene also has great potential for flame retardant applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, some problems faced by 2D nanomaterials, such as the interlayer van der Waals forces, make them prone to forming agglomerates, and smooth and inert surfaces are not conducive to their dispersion in the matrix, which seriously affect the comprehensive properties of the composite materials. 28 LDHs systems can be used to improve the compatibility of twodimensional materials with a polymer matrix due to their rough surface and abundance of oxygen-containing groups. Generally, ZIF-67 is firstly anchored on 2D nanomaterials and then transferred into NiCo-LDH.…”
Section: Industrial Chemistry and Materialsmentioning
confidence: 99%
“…In addition, copper ions can cause the catalytic conversion of CO to CO 2 via the Mars-van Krevelen mechanism to diminish the CO emission. 28,58 To improve the compatibility of LDHs to enhance their fire safety in epoxy composites, Hu et al synthesized hollow dodecahedral NiCo-LDH@PZS with ZIF-67 as a precursor and a sacrificial template, and polyphosphazene (PZS) as an interface compatibilizer and flame retardant. 32 PZS has excellent free radical trapping capacity as well as char formation effect, and synergies with NiCo-LDH significantly inhibit the smoke toxicity generated during the combustion process of EP composites and promote the formation of graphitized residual char.…”
Section: Endowing the Synergist Effectmentioning
confidence: 99%